IMMORTAL MOTIVATIONS IN THE WORKS OF WORLD COMPOSER D. SHOSTAKOVICH IN THE LIGHT OF TODAY'S YOUNG COMPOSERS(F. NAZAROV) - Farkhodjon Nazarov Allaberdiyevich (Scholar Express Journal, 2022)
This article is by world composer d. the immortal motifs in shostakovich’s work are about young composers today. Each work has its own style and genre, artistic image, content and drama. Of course, the musical aesthetic taste, strong technical skills and, of course, the musical feeling play an important role in the performance of musical works. Naturally, the performer must have a certain level of knowledge and skills in conveying the musical idea conceived by the composer to the fans. In performing these works, all aspects of the technical skills of the pianists, i.e. the rapid and intense movement of the fingers, have a positive effect and develop it by directing it to the necessary technical resource. We can say that it is completely different from the piano works of Uzbek composers. Currently, our performers are waiting for national innovative works written for the new piano, and sometimes, if our pianists participate in certain international competitions, of course, in the conditions of the competition, the participant must perform the works of the host country composer. A brief look at the analysis of the work is appropriate.
Keywords: Composer; folk spirituality; creativity; motive